The structural elements controlling the subsurface mineralization as deduced from the integration of magnetic and self-potential methods, Wadi Khosh El-Daba area, southern Sinai, Egypt - YOUSEF, Mohamed H. M. (Contributions to Geophysics and Geodesy, 2024)
Significant copper mineralization are observed to be associated, in most cases, with some radioactive anomalies related to increased uranium and thorium contents in Southern Sinai, Egypt. These mineralizations are related to intense post-magmatic, structurally controlled hydrothermal activities in many localities. Wadi Khosh El-Daba area is one of these locations which is mainly composed of monzogranites dissected by andesite dyke and pegmatite vein. This work deals with the application of ground magnetic and self-potential methods to establish the magnetic sources governing the mineralization, to interpret the significant trends that affected the study area, and to delineate the mineralized zones. The magnetic data were processed, enhanced and interpreted using advanced techniques, such as the first-order vertical derivative (FVD), the tilt derivative (TD), Euler deconvolution (ED), and source parameter image (SPI). The main structural lineaments/contacts that control the distribution of hydrothermal alterations and mineral distributions are oriented to the NW–SE, NE–SW, and NNW–SSE directions. The self-potential (SP) data show that there are numerous mineralized zones; most of them are distributed mainly along the structural lineaments deduced from the magnetic study. The quantitative interpretation revealed that the mineralized bodies are at shallow depths ranging from 5.6 m to 12.7 m, with half-width from 5 m to 13 m. These bodies are shallow to moderate dipping towards the south and north directions. Based on this study an anomaly map is originated to locate the preferred structural elements that may be controlling the mineralization in the area for further future exploration.